1989
DOI: 10.1203/00006450-198904000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor/Cachectin and Interleukin-1 Secretion by Cord Blood Monocytes from Premature and Term Neonates

Abstract: ABSTRACT. Blood monocytes produce two well-defined cytokines, tumor necrosis factor/cachectin (TNF) and 11-1, that have multiple immunologic and inflammatory functions. This study examined the secretion of these cytokines by cord blood monocytes from preterm and term neonates stimulated with or without lipopolysaccharide (LPS). Seventeen samples (eight preterm, nine term) were collected. Supernatants of monocytes were assayed for activities of IL-1 (mitogenesis for mouse thymocytes) and TNF (cytotoxicity for L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(58 citation statements)
references
References 12 publications
6
49
3
Order By: Relevance
“…In summary, cord blood lymphocytes not only produce a lesser amount of TNF (English et al, 39 Weatherstone and Rich, 40 present study), but they are also less susceptible to TNF-␣-induced apoptosis. The decreased susceptibility to TNF-␣-induced apoptosis in cord blood lymphocytes is associated with decreased expression of TNFR-I and certain adapter molecules, and with decreased expression and activity of both initiator and effector caspases.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In summary, cord blood lymphocytes not only produce a lesser amount of TNF (English et al, 39 Weatherstone and Rich, 40 present study), but they are also less susceptible to TNF-␣-induced apoptosis. The decreased susceptibility to TNF-␣-induced apoptosis in cord blood lymphocytes is associated with decreased expression of TNFR-I and certain adapter molecules, and with decreased expression and activity of both initiator and effector caspases.…”
Section: Discussionsupporting
confidence: 47%
“…However, cord blood mononuclear cells have been shown to produce lower amounts of TNF-␣ as compared to peripheral blood mononuclear cells. 39,40 The role of activation of NF-B in decreased TNF-␣-induced apoptosis in cord blood T cells remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced mRNA expression and protein production of TNF-␣ in antigen-or mitogen-stimulated cord vs adult blood monocytes and MNCs were described by others and we confirmed that PPD also had a low effect on CB monocytes, whereas stimulated AB monocytes produced significant TNF-␣ levels in culture supernatant. 9,[18][19][20] CB lymphocytes are known to be naive cells compared to AB lymphocytes as revealed by CD45RA + expression. 15,21,22 In our study, analysis of the monocyte populations showed that both CB and AB monocytes contained a low proportion of CD45RA + cells, but AB mono- cytes also presented a memory profile as determined by the specific marker CD45RO (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Peripheral blood monocytes belonged to the mononuclear phagocytic system which plays a crucial role in phagocytosis and in accessory and immunoregulatory functions. These cells are known to produce a variety of soluble mediators like IL-1␤ and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%